Comparison of Maternal Sleep Quality in Postpartum Period between Vaginal Delivery and Cesarean Section - Ziba Raeesi Dehkordi; Morvarid Ghasab Shirazi; Masoomeh Alidoosti; Mahdi Raee; Masoomeh Del Aram; Mandana Mir Mohammad Ali; Mohammad Rahimi Madiseie (Golestan University of Medical Sciences, 2013)
Background and objective : Postpartum is a critical and stressful period accompanying by fatigue, mood changes and sleep disorders. The purpose of this study was to describe sleep during the second and sixth week of postpartum in the women with cesarean and those with vaginal delivery.   Material and Methods: This cross-sectional study was conducted on 96 women in the second and sixth week of postpartum period (48 after cesarean and 48 after vaginal delivery). The instruments were demographic data sheet and Pittsburgh Sleep Quality Scale .   Results: The Results show that the subjects are correlated with each other on the basis of both parents' and neonates' demographic characteristics.Variables such as subjective sleep quality, sleep latency, actual sleep time , sleep efficiency , sleep disturbance , and daily disfunctioning indicator are significantly different in two groups. The mean of Pittsburgh Sleep Quality Index for vaginal delivery is higher than that of cesarean, which can be a good reason for better sleep quality of the women with vaginal delivery.   Conclusion: Mothers with Cesarean have lower sleep quality than those with normal delivery therefore, they should be educated to select normal delivery and intervened for improving sleep quality in postpartum period.